Directive Act in Team Dynamic: A Pragmatic Study in The Expendables 4 Movie (2023) - Faustine Engelberto; Rahman Taufiqrianto Dako; Fahria Malabar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This research addresses the limitations of pragmatic studies focusing on directive acts within the high-pressure context of modern military action movies. The study aims to investigate the types and situational aspects of the functions of directive acts used by main characters in The Expendables 4 (2023). Employing a qualitative descriptive method, the research integrates Searle's (1975), taxonomy directive acts with Leech's (1983) framework of situational aspects to analyze movie dialogue. Data collection involved watching the movie, transcribing relevant scenes, and classifying utterances based on Searle's (1975) and Leech's (1983). The findings revealed 30 directive utterances, categorized into five types: 15 commands, 6 warnings, 4 requests, 3 instructions, and 2 suggestions. Commands were the most dominant form of the data, which reflects the hierarchical and urgent nature of military operations where immediate compliance is critical. The study concludes that situational urgency and combat intensity have a direct impact on the linguistic realization of directive acts, favoring brevity and force over politeness, but cooperative directive acts like requests and suggestions still play a strategic role in team coordination.